2017
DOI: 10.1016/j.jbiotec.2017.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Shear contributions to cell culture performance and product recovery in ATF and TFF perfusion systems

Abstract: Achievement of a robust and scalable cell retention device remains a challenge in perfusion systems. Of the two filtration systems commonly used, tangential flow filtration (TFF) systems often have an inferior product sieving profile compared to alternating tangential flow filtration (ATF) systems, which is typically attributed to the ATF's unique alternating flow. Here, we demonstrate that observed performance differences between the two systems are a function of cell lysis and not the alternating flow as pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
114
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 98 publications
(133 citation statements)
references
References 29 publications
10
114
1
Order By: Relevance
“…We have shown that 20–200 nm particles are associated with product retention on a 0.2 μm membrane . We hypothesize that rather than using a 0.2 μm filter, a larger pore filter would allow the 20–200 nm particles to pass through the membrane, and therefore reduce the amount of product retention.…”
Section: Introductionmentioning
confidence: 95%
“…We have shown that 20–200 nm particles are associated with product retention on a 0.2 μm membrane . We hypothesize that rather than using a 0.2 μm filter, a larger pore filter would allow the 20–200 nm particles to pass through the membrane, and therefore reduce the amount of product retention.…”
Section: Introductionmentioning
confidence: 95%
“…Previously, ATF has been modeled using a series of empirically derived equations where important parameters such as local velocity, pressure drop, and permeate flux are lumped into single average values (Kelly et al, ). The CFD approach presented in this study provided the basis for improved understanding of the impact of operating conditions on factors such as product sieving (Wang et al, ) and membrane utilization (Stressmann & Moresoli, ). A 2D axisymmetric CFD model was developed using experimental membrane resistance as an input for the simulations.…”
Section: Resultsmentioning
confidence: 99%
“…The ATF system has several advantages over the TFF system, and has been used in numerous perfusion processes (Clincke, Mölleryd, Zhang, et al, ; Karst, Steinebach, Soos, & Morbidelli, ; Kelly et al, ). However recent studies have shown that product sieving is not improved with ATF under certain conditions (Wang et al, ). CFD model of the complex spatial and temporal variations in pressure and permeate flow in these systems may provide additional insight and understanding of how operational parameters can affect product sieving for perfusion bioreactors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell retention device used in all perfusion bioreactors was a polyethersulfone (PES) hollow fiber purchased from Spectrum Laboratories (Rancho Dominquez, CA) operated in either ATF (Repligen, Waltham, MA) or TFF mode using a centrifugal pump (Levitronix, Zurich, Switzerland). The two systems had been previously demonstrated to be interchangeable at the benchtop scale (Wang et al, ). All studies were conducted in 3 L glass stirred tank bioreactors at a 2 L working volume (Applikon Biotechnology, Delft, Netherlands).…”
Section: Methodsmentioning
confidence: 99%